ENT 530 Social Media Portfolio: Farh's Dessert / Farah Haziqah Zulkifli - Zulkifli, Farah Haziqah (2021)
The name Farh’s Dessert is from the combined of the name of the owner of the company, (Far + H ) Farah Haziqah Binti Zulkifli and the word ‘Dessert’ which is the products produced by the company. Using a part of the owner name into company name make its looks authentic and human identities. Using the word 'Dessert' will also attract customers to buy products produced by the company. Farh’s Dessert is located at No. 33 Jalan Badik 28, Taman Puteri Wangsa, 81800, Ulu Tiram, Johor. This company is a company that operates from home and online that makes Facebook the main sales and markerting platform.